Comparison of upfront tandem autologous-allogeneic transplantation versus reduced intensity allogeneic transplantation for multiple myeloma - Sahebi, Firoozeh; Dreger, Peter; Schönland, Stefan (Bone marrow transplantation, 2015)
We performed a retrospective analysis of the European Group for Blood and Marrow Transplantation database comparing the outcomes of multiple myeloma patients who received tandem autologous followed by allogeneic PSCT (auto-allo) with the outcomes of patients who underwent a reduced intensity conditioning allograft (early RIC) without prior autologous transplant. From 1996 to 2013, we identified a total of 690 patients: 517 patients were planned to receive auto-allo and 173 received an early RIC allograft without prior autologous transplant. With a median follow-up of 93 months, 5-year PFS survival was significantly better in the auto-allo group, 34% compared with 22% in the early RIC group (P<0.001). OS was also significantly improved in the auto-allo group with a 5-year rate of 59% vs 42% in the early RIC group (P=0.001). The non-relapse mortality rate was lower in the auto-allo group than in the early RIC group, with 1- and 3-year rates of 8% and 13% vs 20% and 28%, respectively (P<0.001). The relapse/progression rate was similar in the two groups, with 5-year rates of 50% for auto-allo and 46% for early RIC (P=0.42). These data suggest that planned tandem autologous allograft can improve overall survival compared with upfront RIC allograft alone in patients with multiple myeloma.